2018
DOI: 10.1007/7651_2018_162
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cancer Stem Cells from Squamous Cell Carcinoma

Abstract: Different cancer stem cell (CSC) populations can be found in many types of cancer, including squamous cell carcinoma (SSC). Diverse reports showed that CSC play a crucial role in the relapse of different types of cancer. CSC sustains tumor growth due to their capacity to self-renew and their potential to initiate secondary tumors with metastatic cancer features. Therefore, the development of methods for the isolation of CSC is a key step to explore the mechanisms underlying CSC maintenance. In this chapter, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Different mouse models of SCC and BCC are widely used for studying stem cell, cancer stem cell, and cancer biology. 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 To determine the relevance of established mouse models to human skin cancer, we first determined whether the mouse SCC stem cell (SCC-SC) signature genes are highly represented in the human SCC. 66 We found that 598 mouse SCC-SC genes with human orthologs were expressed in our human tumor or normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Different mouse models of SCC and BCC are widely used for studying stem cell, cancer stem cell, and cancer biology. 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 To determine the relevance of established mouse models to human skin cancer, we first determined whether the mouse SCC stem cell (SCC-SC) signature genes are highly represented in the human SCC. 66 We found that 598 mouse SCC-SC genes with human orthologs were expressed in our human tumor or normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…SCCs or skin samples from prior SCC locations (n = 42) were dissected and processed as described by Fontenete et al [26]. Single-cell suspensions were stained using different antibodies: CD45-FITC (BD Pharmingen, San Diego, CA), CD3-APC (eBioscience, San Diego, CA), Cd11b-PerCPCy5.5 (eBioscience), B220-PE-Cy7 (eBioscience), Ly6G-PE (Biolegend, San Diego, CA), CD45-FITC (BD Pharmingen), CD8-PE-Cyanine7 (Biolegend), and CD3-APC (eBioscience).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…HF-MSCs CD34 may be to refresh hematopoietic system, as mentioned previously (Lako et al 2002 ). Some studies were focused on the surface marker of HF-MSCs such as integrin, keratin (CK14, CK15, and CK19), C8/144B, p63, CD71 and CX43 (Dong et al 2014 ; Maleki et al 2014 ; Son et al 2015 ), CD34 (Sol et al 2018 ) CD49f (Krebsbach and Villa-Diaz 2017 ) and CD34 and CD49f duel-positive cell residents in mice (Fontenete and Perez-Moreno 2018 ). Babakhani et al (Babakhani et al 2019 ) showed that the bulge of HF-MSCs was nestin and CD34 positive and Kr15 negative.…”
Section: Discussionmentioning
confidence: 99%